Glaciers and Ice Sheets As Analog Environments of Potentially Habitable Icy Worlds - Garcia-Lopez, Eva; Cid, Cristina (Frontiers in Microbiology, 2017)
Icy worlds in the solar system and beyond have attracted a remarkable attention as possible habitats for life. The current consideration about whether life exists beyond Earth is based on our knowledge of life in terrestrial cold environments. On Earth, glaciers and ice sheets have been considered uninhabited for a long time as they seemed too hostile to harbor life. However, these environments are unique biomes dominated by microbial communities which maintain active biochemical routes. Thanks to techniques such as microscopy and more recently DNA sequencing methods, a great biodiversity of prokaryote and eukaryote microorganisms have been discovered. These microorganisms are adapted to a harsh environment, in which the most extreme features are the lack of liquid water, extremely cold temperatures, high solar radiation and nutrient shortage. Here we compare the environmental characteristics of icy worlds, and the environmental characteristics of terrestrial glaciers and ice sheets in order to address some interesting questions: i) which are the characteristics of habitability known for the frozen worlds, and which could be compatible with life, ii) what are the environmental characteristics of terrestrial glaciers and ice sheets that can be life-limiting, iii) What are the microbial communities of prokaryotic and eukaryotic microorganisms that can live in them, and iv) taking into account these observations, could any of these planets or satellites meet the conditions of habitability? In this review, the icy worlds are considered from the point of view of astrobiological exploration. With the aim of determining whether icy worlds could be potentially habitable, they have been compared with the environmental features of glaciers and ice sheets on Earth. We also reviewed some field and laboratory investigations about microorganisms that live in analogue environments of icy worlds, where they are not only viable but also metabolically active.